Seed predation and dispersal by small mammals in a landscape of fear: effects of personality, predation risk and land‐use change. Issue 2 (6th May 2021) - Boone, Sara R.; Brehm, Allison M.; Mortelliti, Alessio
Abstract : Scatter‐hoarding small mammals act as both seed predators and seed dispersers in forest ecosystems. Their choices regarding consuming or caching seeds must balance the risk of predation with the energy rewards gained from immediate or delayed consumption of seeds. Several factors influence their interaction with seeds, including the individual's personality. Little is known about how personality affects foraging decisions in response to predation risk. This missing information is critical because if foraging decisions differ among individuals in response to perceived risk, then varying combinations of personality types in a population (and varying risks of predation across forest types) may have diverse effects on forest regeneration. Further, land‐use change may influence the interplay of personality, risk perception and foraging decisions by altering the distribution of personality types in the landscape and the risk perceived by individuals. To contribute to filling these knowledge gaps, we designed a large‐scale field experiment to evaluate how personality, perceived predation risk and land‐use change affect the interaction of deer mice Peromyscus maniculatus and seeds. Using infrared cameras, we recorded the choices of individuals of known personality at paired experimental sites with high versus low perceived predation risk (n = 2389 observations from 74 individuals). We found that personality influenced multiple foraging decisions, and perceived risk affected how individuals with different personalities responded to those decisions. Specifically, exploration/activity influenced seed choice, boldness affected the number of seeds selected and docility influenced both foraging site selection and whether mice immediately consumed or removed seeds. Since personality only affected foraging microsite selection in unmanaged forests, our results show that land‐use change decreased the importance of personality in affecting risk perception. We demonstrate the importance of considering personality on foraging decisions under varying levels of risk, and more generally, underscore the importance of considering individual variation in affecting ecological processes.